Polymeric compositions for use in electroless plating, methods of electroless plating, and polymeric articles made by electroless plating - Patents.com

By using specific grafted rubber copolymers and ungrafted styrene polymers in the electroplating composition, combining core/shell dienyl rubber and fatty acids and other components, the problems of poor adhesion between the plating layer and the polymer substrate and narrow process window in the electroplating technology are solved, and high-quality plating and good mechanical properties are achieved.

JP7677960B2Active Publication Date: 2025-05-15SABIC GLOBAL TECHNOLOGIES BV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022522313
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-21
Filing Date
2020-10-12
Publication Date
2025-05-15
Estimated Expiration
2040-10-12

AI Technical Summary

Technical Problem

The existing electroplating technology is difficult to maintain good adhesion between the metal plating and the polymer substrate after multiple severe temperature cycles, and it is also difficult to take into account the mechanical properties of the finished polymer products and the quality of the plating in the process window.

Method used

The electroplating composition containing 9-29% of the first grafted rubber copolymer, 70-90% of the ungrafted styrene polymer, 0.1-10% of the core/shell dienyl rubber, 0.1-2% of the fatty acid or salt thereof, and 0-5% of the metal oxide were processed.

Benefits of technology

Good adhesion between the metal plating and the polymer substrate after multiple temperature cycles is achieved, and the mechanical properties of the finished polymer product and the quality of the plating are taken into account in the process window, reducing plating defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007677960000001
    Figure 0007677960000001
  • Figure 0007677960000002
    Figure 0007677960000002
  • Figure 0007677960000003
    Figure 0007677960000003
Patent Text Reader

Abstract

1. An electroless plating composition comprising: 9 to 29 weight percent, 9.7 to 29 weight percent, or 10 to 29 weight percent of a first graft rubber copolymer comprising at least one conjugated diene monomer and at least one monovinyl aromatic monomer in polymerized form; 70 to 90 weight percent, preferably 70 to 89.7 weight percent, more preferably 70 to 85 weight percent of an ungrafted styrene polymer; 0.1 to 10 weight percent of a core / shell diene-based rubber having a particle size of 100 to 500 nanometers (nm); one or more stabilizers and / or antioxidants in a total amount of 0.1 to 5 weight percent; a fatty acid or a fatty acid salt in an amount of 0.1 to 2 weight percent; 0 to 5 weight percent of a mold release agent; 0 to 1 weight percent of a metal oxide; 0 to 3 weight percent of a lubricant; and 0 to 20 weight percent of a polycarbonate, wherein the weight percents and ppm are based on the total weight of the composition. The composition can be formed into an article having an electrolessly plated metal coating thereon.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Metal plating of plastic articles is used in a variety of fields. For example, in the electronics field, electroless plating has been used to form conductive plated through holes in printed circuit boards. As a further example, in the automotive industry, chrome plating of polymeric parts is used to fabricate various automotive parts. In certain applications, the fabricated articles are exposed to a wide range of temperatures during use, during which the coating must retain good adhesion to the substrate. For example, metal plated polymeric automotive parts may be exposed to temperatures well below 0°C and well above 90°C.

[0002] A challenge facing current electroless plating is to obtain an article in which there is sufficient adhesion between the metal plating and the polymeric substrate even after repeated severe temperature cycling. Yet another challenge facing current electroless plating is to provide a composition that allows a reasonably wide process window for the formation of the article (e.g., by injection molding) and subsequent electroless plating (which is typically followed by electrolytic plating, i.e., electroplating, of an additional metal layer) while providing good properties in the final article. Examples of potentially important properties of the article include one or more of the following in the final article: impact strength, tensile strength, tensile modulus, flexural modulus, coefficient of thermal expansion, uniform highly reflective appearance, and good adhesion between the metal coating and the polymeric substrate. Summary of the Invention

[0003] Disclosed herein is an electroless plating composition comprising from 9 to 29 weight percent, preferably from 9.7 to 29 weight percent, more preferably from 10 to 29 weight percent of a first graft rubber copolymer having a backbone comprising at least one conjugated diene monomer in polymerized form and grafted to the backbone at least one monomer in polymerized form selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof; from 70 to 90 weight percent, preferably from 70 to 89.7 weight percent, more preferably from 70 to 85 weight percent of a first graft rubber copolymer having at least one conjugated diene monomer in polymerized form and grafted to the backbone at least one monomer in polymerized form selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof; A composition for electroless plating comprising a styrene polymer not grafted to a polymerized conjugated diene rubber; 0.1-10 weight percent of a core / shell diene rubber having a particle size of 100-500 nanometers (nm); 0.1-5 weight percent total of one or more stabilizers and / or antioxidants; 0.1-2 weight percent of a fatty acid or a salt of a fatty acid; 0-5 weight percent of a mold release agent; 0-1 weight percent of a metal oxide; 0-3 weight percent of a lubricant; and 0-20 weight percent of a polycarbonate, the weight percents and ppm being based on the total weight of the composition. Alternatively, the amounts of the components expressed above may be in parts by weight.

[0004] Also disclosed are articles comprising the composition. The article can have an electrolessly plated metal coating thereon.

[0005] Also disclosed is a method of making such an article, comprising forming the composition into a desired shape and electrolessly plating one or more metals onto the formed composition. The electroless plating process can include an etching step using an oxidizing acid. The electroless plating step can be followed by electroplating (e.g., electrolytic plating) one or more additional metal layers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Although acrylonitrile / butadiene / styrene graft rubber (ABS) compositions can be electrolessly plated, there remains a need for compositions that exhibit one or more of the following properties, either alone or in combination: good adhesion (especially after thermal cycling) with electrolessly or electrolytically plated metal coatings thereon, a wide processing window for forming articles from the composition (e.g., by injection molding), a wide processing window for subsequently electrolessly plating such articles to result in articles with no or few defects in the metal coating, and good mechanical properties in the final article, such as impact strength, tensile strength, tensile modulus, flexural modulus, etc. The coefficient of thermal expansion can be such that the composition can be useful in electrolessly plated articles.

[0007] Various compositions have been presented. For example, WO2013 / 116903 provides examples of electroplated compositions that include polycarbonate (PC), at least a first ABS impact modifier, and a second impact modifier that is chemically different from the first impact modifier. WO2013 / 115903 discloses that when a composition having PC and two impact modifiers also includes poly(styrene acrylonitrile) (SAN), and ABS is not used in either of the two impact modifiers, the adhesive strength of the plated sample is reduced compared to a composition that includes a single ABS modifier. In addition, WO2013 / 115903 shows that the addition of methacrylate butadiene styrene (MBS) as a second impact modifier to a composition of ABS and PC reduces the adhesive strength of the plated sample when the polycarbonate content is reduced. Surprisingly, in light of the teachings of WO2013 / 116903 regarding formulations with reduced adhesion, the compositions disclosed herein comprising 9 to 29 weight percent, preferably 9.7 to 29 weight percent, more preferably 10 to 29 weight percent of a graft rubber of at least one conjugated diene monomer and at least one monovinyl aromatic monomer, 70 to 90 weight percent, preferably 70 to 89.7 weight percent, more preferably 70 to 85 weight percent of an ungrafted styrene polymer, 0.1 to 10 weight percent of a core / shell diene rubber having a particle size of 100 to 500 nm, and a fatty acid or a salt of a fatty acid in an amount of 0.1 to 2 weight percent, show good adhesion (including after thermal cycling) when compared to similar compositions excluding the core / shell butadiene rubber. The total amount of conjugated diene-based rubber (e.g., the backbone of the first graft rubber copolymer and the diene-rubber core of the core / shell diene-based rubber) in the composition can be 10 to 20 weight percent based on the total weight of the composition. Alternatively, the amounts of the components expressed above can be in parts by weight.

[0008] First Graft Rubber Copolymer Grafted rubber copolymers, such as ABS, contain two or more polymeric moieties of different composition that are chemically bonded. Such grafted rubber copolymers can be prepared by first polymerizing a conjugated diene, such as butadiene or another conjugated diene, optionally with a monomer copolymerizable therewith, such as styrene, to provide a polymeric backbone. After the polymeric backbone is formed, at least one, and preferably two, grafting monomers are polymerized in the presence of the polymeric backbone to obtain the grafted copolymer. These resins can be prepared by methods well known in the art, for example, by emulsion or suspension radical polymerization.

[0009] The polymer backbone is preferably a conjugated diene polymer such as polybutadiene, polyisoprene, or a copolymer such as butadiene-styrene, butadiene-acrylonitrile, or the like.

[0010] The conjugated diene monomers typically utilized in preparing the polymeric backbone of the graft copolymers have the following formula (I): [ka] Wherein, X b is hydrogen, C1-C5 alkyl, chlorine, bromine, etc. Examples of conjugated diene monomers that can be used are butadiene, isoprene, 1,3-heptadiene, methyl-1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-pentadiene; 1,3- and 2,4-hexadiene, chloro- and bromo-substituted butadienes such as dichlorobutadiene, bromobutadiene, dibromobutadiene, mixtures containing at least one of the aforementioned conjugated diene monomers, etc. The preferred conjugated diene monomer is butadiene.

[0011] One monomer or group of monomers that can be polymerized in the presence of the polymer backbone are the monovinyl aromatic hydrocarbons. The monovinyl aromatic monomers utilized are represented by the following formula (II): [ka] Wherein, X c is hydrogen, C1-C 12 Alkyl (including cycloalkyl), C6-C 12 Aryl, C7-C 12 Aralkyl, C7~C 12 Alkaryl, C1-C 12 Alkoxy, C6-C 12 aryloxy, chlorine, bromine, etc. Examples of monovinyl aromatic monomers include styrene, 3-methylstyrene, 3,5-diethylstyrene, 4-n-propylstyrene, alpha-methylstyrene, alpha-methylvinyltoluene, alpha-chlorostyrene, alpha-bromostyrene, dichlorostyrene, dibromostyrene, tetra-chlorostyrene, mixtures comprising at least one of the foregoing compounds, etc. A preferred monovinyl aromatic monomer is styrene.

[0012] A second group of monomers that can be polymerized in the presence of the polymeric backbone are acrylic monomers such as acrylonitrile or substituted acrylonitriles.

[0013] Acrylonitrile and substituted acrylonitrile are represented by the following formula (III): [ka] Wherein, X b is as previously defined, and Y 2 is cyano, etc. Examples of such monomers include acrylonitrile, ethacrylonitrile, methacrylonitrile, alpha-chloroacrylonitrile, beta-chloroacrylonitrile, alpha-bromoacrylonitrile, beta-bromoacrylonitrile, mixtures containing at least one of the foregoing monomers, etc. The preferred monomer is acrylonitrile.

[0014] In preparing the graft copolymer, the polymeric backbone (e.g., derived from the conjugated diene monomer and optional monovinyl aromatic and / or acrylic comonomers) can comprise at least 15 weight percent, or at least 20 weight percent, up to 65 weight percent, or up to 60 weight percent, or up to 50 weight percent of the total weight of the graft copolymer composition. For example, the graft copolymer composition can include 15 to 65 weight percent, or 15 to 60 weight percent, or 15 to 50 weight percent, or 20 to 65 weight percent, or 20 to 60 weight percent, or 20 to 50 weight percent of the polymeric backbone derived from the conjugated diene monomer, based on the total weight of the graft copolymer composition. The monomers polymerized in the presence of the polymeric backbone, exemplified by styrene and acrylonitrile, can comprise from 35 weight percent, or from 40 weight percent, or from 50 weight percent, up to 85 weight percent, or up to 80 weight percent, based on the total weight of the total graft polymer composition. For example, the graft copolymer composition may comprise 35 to 85 weight percent, or 40 to 90 weight percent, of one or more comonomers selected from monovinyl aromatic monomers and acrylic monomers. The acrylic monomers of the graft polymer composition, exemplified by acrylonitrile, may comprise 5 to 40 weight percent of the total graft copolymer composition. The monovinyl aromatic hydrocarbons, exemplified by styrene, may comprise 10 to 70 weight percent of the total graft copolymer.

[0015] However, in preparing a graft copolymer composition, it is common to have a certain percentage of polymerized monomers that are grafted onto the polymer backbone combine with each other and exist as free copolymers. For example, if one utilizes styrene as one of the grafted monomers and acrylonitrile as the second grafted monomer, a certain portion of the composition will copolymerize as a free, i.e., ungrafted, styrene-acrylonitrile copolymer. If alpha-methylstyrene (or other monomer) is substituted for styrene in the composition used to prepare the graft polymer, a certain percentage of the composition may be an alpha-methylstyrene-acrylonitrile copolymer. Thus, the grafted copolymer itself (not including free polymer or copolymer of monomers polymerized in the presence of the backbone) can contain from 55 weight percent, or from 60 weight percent, to 80 weight percent, or from 75 weight percent, or to 70 weight percent of a backbone comprising conjugated diene monomer in polymerized form, and can contain from 20 weight percent, or from 25 weight percent, to 50 weight percent, or from 45 weight percent, or to 40 weight percent of polymerized monomer in polymerized form grafted to the backbone. For example, the grafted copolymer can contain 55-75 weight percent or 60-70 weight percent of a backbone derived from a conjugated diene monomer, and can contain 25-45 weight percent or 30-40 weight percent of a copolymer of one or more monomers of formula II and / or III grafted to the backbone.

[0016] The first rubber graft copolymer composition may be acrylonitrile / butadiene / styrene. The ABS copolymer composition may include 20 to 65 weight percent butadiene-based content (i.e., derived from butadiene monomer) based on the total weight of the ABS copolymer. The weight ratio of styrenic content (i.e., derived from styrene) to acrylonitrile-based content (i.e., derived from acrylonitrile) may be at least 65:35. The weight ratio of styrenic content to acrylonitrile content may be 80:20 or less. However, in the graft copolymer itself (excluding free polystyrene, free acrylonitrile, or free styrene-acrylonitrile not grafted to the butadiene-based backbone), the weight percent of the butadiene-based content can be from 55, or 60, to 80, to 75, or to 70 weight percent of the graft copolymer, and the grafted styrene-acrylonitrile can be from 20, to 25, or 30, to 45, or to 40 weight percent based on the total weight of the graft copolymer. The graft portion (i.e., the styrene-acrylonitrile grafted to the butadiene-derived backbone) can be 40 to 60, or 45 to 55 weight percent based on the weight of the backbone.

[0017] The first rubber graft copolymer can have a particle size of at least 50 nanometers, or at least 100 nanometers. The first rubber graft copolymer can have a particle size of 1000 nanometers, or up to 800 nanometers. The particle size can be measured by light scattering UV-visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and the like. The average particle size can be determined according to ASTM D1417 (2010). The first rubber graft copolymer can have a gel content of at least 10%. The first rubber graft copolymer can have a gel content of up to 50%. The gel content can be measured by D2765-16 using tetrahydrofuran (THF) or acetone as the solvent. The first rubber graft copolymer can be ABS as described herein with a particle size and / or gel content as described herein.

[0018] The amount of the first rubber graft copolymer can be at least 9 weight percent, preferably at least 9.7 weight percent, more preferably at least 10 weight percent, even more preferably at least 15 weight percent, up to 29 weight percent, or up to 25 weight percent based on the total weight of the composition. The amount of the first rubber graft copolymer composition (including the ungrafted polymer of the monomer to be grafted to the backbone) can be from 10 to 59 weight percent, or up to 55 weight percent, or up to 50 weight percent based on the total weight of the composition. For example, the composition can be made using a first rubber graft copolymer composition exemplified by ABS (including free, ungrafted, and SAN) in an amount of 10-59 weight percent, or 20-55 weight percent, or 30-55 weight percent, or 35-50 weight percent based on the total weight of the composition.

[0019] Core / shell diene rubber The composition further includes a core-shell diene based rubber that differs from the first rubber graft copolymer in its chemical composition, its morphology, or both.

[0020] The core of the core-shell diene rubber comprises a polymer or copolymer of a conjugated diene monomer such as those in formula (I). For example, the core may comprise polybutadiene, polyisoprene, or copolymers such as butadiene-styrene, butadiene-acrylonitrile, and the like. According to a preferred embodiment, the core is polybutadiene. The core may be at least 70 percent by weight, or at least 80 percent by weight, of the core / shell diene rubber, based on the total weight of the rubber. The core may be up to 95 percent by weight, or up to 90 percent by weight, of the core / shell diene rubber, based on the total weight of the rubber. For example, the core / shell diene rubber may comprise a core, as exemplified by polybutadiene, in an amount of 70 to 95 percent by weight, or 80 to 95 percent by weight, or 75 to 90 percent by weight, based on the total weight of the core / shell diene rubber.

[0021] The shell is grafted to the core. The shell comprises one or more vinyl aromatic monomers according to formula (II) in polymerized form and / or a vinyl aromatic monomer according to formula (IV): [ka] In one embodiment, the copolymer may include one or more acrylic monomers, such as those shown in the formula: b is as previously defined, and Y 2 Cyano, C1-C 12 alkoxycarbonyl, etc. Examples of such monomers include acrylonitrile, ethacrylonitrile, methacrylonitrile, alpha-chloroacrylonitrile, beta-chloroacrylonitrile, alpha-bromoacrylonitrile, beta-bromoacrylonitrile, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, propyl acrylate, isopropyl acrylate, mixtures comprising at least one of the foregoing monomers, and the like.

[0022] Examples of such acrylic monomers include acrylic acid esters exemplified by acrylonitrile, substituted acrylonitrile, and / or acrylonitrile, as well as C1-C7 alkyl acrylates such as methyl methacrylate. Acrylates such as methyl methacrylate are preferred.

[0023] The core / shell diene rubber may have at least 5 weight percent, or at least 10 weight percent, of one or more acrylic monomer content. The core / shell diene rubber may have up to 29 weight percent, or up to 20 weight percent, of one or more acrylic monomer content, based on the total weight of the rubber. The core / shell diene rubber may have at least 0.1 weight percent, or at least 0.5 weight percent, or at least 1 weight percent, or at least 2 weight percent, of one or more monovinyl aromatic monomer content, based on the total weight of the core / shell diene rubber. The core / shell diene rubber may have up to 10 weight percent, or up to 5 weight percent, of one or more monovinyl aromatic monomer content, based on the total weight of the rubber. For example, the core / shell diene rubber may contain 5 to 29 weight percent or 5 to 20 weight percent of an acrylic monomer exemplified by methyl methacrylate, and 0.1 to 10 weight percent of a monovinyl aromatic monomer exemplified by styrene, based on the total weight of the core / shell diene rubber.

[0024] Preferably, the core / shell diene rubber is methyl methacrylate / butadiene / styrene (MBS). The core / shell MBS rubber may comprise at least 70 weight percent, or at least 80 weight percent, of a polybutadiene core based on the total weight of the MBS. The core / shell MBS rubber may comprise up to 95 weight percent, or up to 90 weight percent, of a polybutadiene core based on the total weight of the MBS. The amount of methyl methacrylate content may be at least 5 weight percent, or at least 10 weight percent, based on the total weight of the MBS. The amount of methyl methacrylate content may be up to 29 weight percent, or up to 20 weight percent, based on the total weight of the MBS. The amount of monovinyl aromatic (e.g., styrene) content may be at least 0.1 weight percent, or at least 0.5 weight percent, or at least 1 weight percent, or at least 2 weight percent, based on the total weight of the MBS. The amount of monovinyl aromatic content may be up to 10 weight percent, or up to 5 weight percent, based on the total weight of the MBS. For example, the core / shell diene rubber may contain 70 to 95 weight percent of a polybutadiene core, 5 to 20 weight percent of a methyl methacrylate content as part of the shell, and 0.1 to 5 weight percent of a styrene content, based on the total weight of the MBS.

[0025] The core / shell diene rubber is characterized by relatively small particle size of the core / shell particles. The core / shell diene rubber particles can have an average size of at least 100 nanometers (nm). The core / shell diene rubber particles can have an average size of up to 500 nm, or up to 400 nm, or up to 300 nm. For example, the particles can have an average size of 100-500 nm, or 100-400 nm. The particle size can be measured by light scattering according to ASTM B822-17.

[0026] The inclusion of a small core / shell diene based rubber in addition to the first graft rubber copolymer is believed to facilitate one or more of modifying or controlling the rheology of the composition during processing (e.g., injection molding), controlling pore size during etching as part of the electroless plating process, impact strength (especially at low temperatures), and crack resistance.

[0027] The amount of the core / shell diene rubber is at least 0.1 weight percent, or at least 0.5 weight percent, or at least 1 weight percent, or at least 2 weight percent, or at least 3 weight percent based on the total weight of the composition. The amount of the core / shell diene rubber is up to 10 weight percent, or up to 9 weight percent, or up to 8 weight percent, or up to 7 weight percent, or up to 6 weight percent, or up to 5 weight percent based on the total weight of the composition. For example, the composition can include the core / shell diene rubber in an amount of 0.1 to 10 weight percent, or 0.5 to 9 weight percent, or 1 to 8 weight percent, or 1 to 7 weight percent, or 2 to 6 weight percent, or 3 to 5 weight percent based on the total weight of the composition. Too much small particle size core-shell rubber present in the formulation with less large particles, the ABS graft rubber, can lead to non-optimal etching and non-optimal pore size distribution, resulting in reduced plating adhesion.

[0028] Ungrafted styrene polymers and copolymers. Although the first graft rubber composition may contain some free styrene polymer remaining from the process of making the first graft rubber composition, the compositions disclosed herein have the styrene polymer present in an amount of 70 to 90 weight percent, preferably 70 to 89.7 weight percent, and more preferably 70 to 85 weight percent based on the total weight of the composition. Thus, some ungrafted styrene polymer is added to the first graft rubber composition and the small particle size core-shell rubber.

[0029] The term "styrene polymer" (which includes styrene copolymers), as used herein, includes polymers prepared by methods known in the art, including bulk, suspension, and emulsion polymerization, with one or more monovinyl aromatic hydrocarbons of formula (II). The styrene copolymers may be random or block copolymers. Examples of monovinyl aromatic monomers include styrene, 3-methylstyrene, 3,5-diethylstyrene, 4-n-propylstyrene, alpha-methylstyrene, alpha-methylvinyltoluene, alpha-chlorostyrene, alpha-bromostyrene, dichlorostyrene, dibromostyrene, tetra-chlorostyrene, mixtures containing at least one of the foregoing compounds, and the like. A preferred monovinyl aromatic monomer is styrene.

[0030] These polymers may include comonomers such as vinyl monomers, acrylic monomers (including methacrylic monomers), maleic anhydride and derivatives, and the like, and combinations thereof. As defined herein, a vinyl monomer is an aliphatic compound having one or at least one polymerizable carbon-carbon double bond. Suitable vinyl monomers include, for example, ethylene, propylene, butenes (including 1-butene, 2-butene, and isobutene), pentene, hexene, and the like, and combinations thereof.

[0031] Acrylic monomers include, for example, acrylonitrile, ethacrylonitrile, methacrylonitrile, α-chloroarylonitrile, β-chloroacrylonitrile, α-bromoacrylonitrile, and β-bromoacrylonitrile, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, propyl acrylate, isopropyl acrylate, and the like, and mixtures thereof. The nitrile monomers of acrylonitrile can often provide improved solvent resistance.

[0032] Maleic anhydride and its derivatives can include, for example, maleic anhydride, maleimide, N-alkylmaleimide, N-arylmaleimide, or alkyl or halo substituted N-arylmaleimide, etc., and combinations thereof. Acrylonitrile is a preferred comonomer.

[0033] The amount of comonomer(s) present in the styrene copolymer may vary. The copolymer may contain at least 50 weight percent, or at least 60 weight percent, or at least 65 weight percent of content derived from monovinyl aromatic monomers (e.g., amount of polymerized styrene monomer). The copolymer may contain up to 90 weight percent, or up to 85 weight percent, or up to 80 weight percent of content derived from monovinyl aromatic monomers such as styrene. The copolymer may contain at least 10 weight percent, or at least 15 weight percent, or at least 20 weight percent, up to 40 weight percent, up to 50 weight percent, or up to 35 weight percent of content derived from the comonomers identified above (e.g., substituted or unsubstituted acrylonitrile). The weight percent of content derived from monomer(s) is based on the total weight of the styrene copolymer. For example, a styrenic polymer may contain from 50 to 90 percent polymerized monovinyl aromatic monomer (exemplified by styrene) and from 10 to 50 weight percent polymerized comonomer (exemplified by acrylonitrile), based on the total weight of the styrenic polymer.

[0034] One preferred polystyrene copolymer resin is poly(styrene acrylonitrile), or SAN, which can have a weight average molecular weight of 50,000 to 160,000 g / mol, as measured by gel permeation chromatography (GPC) according to ASTM D5296-11 using polystyrene standards.

[0035] The amount of ungrafted styrene polymer in the composition (including any amount of ungrafted styrene polymer provided as part of the first graft rubber copolymer composition) is 70 to 90 weight percent, preferably 70 to 89.7 weight percent, more preferably 70 to 85 weight percent based on the total weight of the composition. If the first graft rubber copolymer composition and / or the core-shell has a high rubber content (e.g., the first graft rubber copolymer has a high rubber backbone), more free styrene can be added to reach a total rubber content in the composition in the range of 10 to 20 weight percent based on the total weight of the composition.

[0036] Fatty acids or fatty acid salts The composition may further comprise one or more fatty acids or salts of fatty acids. Fatty acids are organic acids having 8 to 40 carbon atoms. Salts are salts of such acids. Thus, fatty acids may have the formula R-COOH and salts may have the formula R-COOM, where R is a hydrocarbon having at least 8, or at least 40, or up to 36, or up to 30, or up to 24, or up to 20 carbon atoms, and M is a metal ion. R may be a saturated or unsaturated hydrocarbon, and may be straight or branched, but is often straight. R may be an alkyl. R may be an alkenyl. If the number of carbon atoms is too low, the fatty acid may become too volatile. If the number of carbon atoms is too high, the fatty acid may not be sufficiently compatible in the polymer composition. Mixtures of fatty acids may be used. Examples of suitable fatty acids and their salts include myristic acid, linoleic acid, palmitic acid, oleic stearic acid, elaidic acid, stearic acid, and their salts, and any combinations thereof.

[0037] Alkali metal fatty acid salts are preferred. Fatty acid salts of lead, mercury, thallium, cadmium, barium, or antimony should be avoided due to potential toxicity and undesirable environmental effects.

[0038] The fatty acid or fatty acid salt can aid in the dispersion of diene rubber particles in the composition and can also provide a metal releasing effect.

[0039] The total amount of all fatty acids and fatty acid salts is at least 1000 ppm, or at least 2000 ppm, or at least 3000 ppm based on the total weight of the composition. The total amount of all fatty acids and fatty acid salts is 20,000 ppm or less, or 15,000 ppm or less, or 10,000 ppm or less based on the total weight of the composition. For example, the composition can contain fatty acids and fatty acid salts in an amount of 1000 to 20,000 ppm, or 2000 to 15,000 ppm, or 3000 to 10,000 ppm based on the total weight of the composition. If too much fatty acid is present, problems of juicing (or liquid forming on the mold) may occur in the injection molding process.

[0040] Antioxidants and Stabilizers The disclosed composition may further comprise one or more antioxidants. Examples of antioxidants include hindered phenols, secondary arylamines, phosphorus-containing compounds such as phosphites or phosphonates, sulfur-containing compounds such as thioesters, or any combination thereof. More specific examples of the antioxidant additives include organic phosphites, such as tris(nonylphenyl)phosphite, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, and the like; alkylated monophenols or polyphenols; alkylation reaction products of polyphenols and dienes, such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane, and the like; butylation reaction products of para-cresol or dicyclopentadiene; alkylated hydroquinones; hydroxylated thiodiphenyl ethers; alkylidene-bisphenols; benzyl compounds; beta-(3,5-di-tert-butyl-4-hydroxyhydrocinnamate); esters of beta-(5-tert-butyl-4-hydroxy-3-methylphenyl)-propionic acid with mono- or polyhydric alcohols; esters of thioalkyl or thioaryl compounds; such as distearyl thiopropionate, dilauryl thiopropionate, ditridecyl thiodipropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythrityl-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and the like; amides of beta-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionic acid, and the like, or combinations comprising at least one of the foregoing antioxidants. If an antioxidant is used, it may be included in an amount of at least 0.01 weight percent, or at least 0.05 weight percent, or at least 0.1 weight percent, up to 5 weight percent, or up to 3 weight percent, or up to 1 weight percent based on the total weight of the composition.For example, the composition can include the antioxidant in an amount of 0.01 to 5 weight percent, or 0.05 to 3 weight percent, or 0.1 to 1 weight percent, based on the total weight of the composition.

[0041] Suitable stabilizer additives, including heat or light stabilizers.

[0042] Examples of heat stabilizers include organic phosphites, such as triphenyl phosphite, tris-(2,6-dimethylphenyl) phosphite, tris-(mixed mono- and di-nonylphenyl) phosphites, and the like; phosphonates, such as dimethylbenzene phosphonate, and the like; organic phosphates, such as trimethyl phosphate; thioesters, such as pentaerythritol beta lauryl thiopropionate, and the like; or combinations comprising at least one of the aforementioned heat stabilizers. When a heat stabilizer is used, the heat stabilizer may be included in an amount of at least 0.01 weight percent, or at least 0.05 weight percent, or at least 0.1 weight percent, up to 5 weight percent, or up to 3 weight percent, or up to 1 weight percent, based on the total weight of the composition. For example, the composition may include the heat stabilizer in an amount of 0.01 to 5 weight percent, or 0.05 to 3 weight percent, or 0.1 to 1 weight percent, based on the total weight of the composition.

[0043] Plated parts are usually protected from photochemical reactions, but light stabilizers and / or ultraviolet light (UV) absorbing additives may also be used, especially if the part is only partially plated. Suitable light stabilizer additives include, for example, benzotriazoles, such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)-benzotriazole, and 2-hydroxy-4-n-octoxybenzophenone, hindered amine light stabilizers (HALS), and the like, or combinations comprising at least one of the foregoing light stabilizers. When light stabilizers are used, the light stabilizer may be included in an amount of 0.01 weight percent, or at least 0.05 weight percent, or at least 0.1 weight percent, up to 10 weight percent, or up to 5 weight percent, or up to 3 weight percent, based on the total weight of the composition. For example, the composition may include the light stabilizer in an amount of 0.01 to 5 weight percent, or 0.05 to 3 weight percent, or 0.1 to 1 weight percent, based on the total weight of the composition. Suitable UV absorbing additives include, for example, hydroxybenzophenones; hydroxybenzotriazoles; hydroxybenzotriazines; cyanoacrylates; oxanilides; benzoxazinones; 2-(2H-benzotriazol-2-yl)-4-(l,l,3,3-tetramethylbutyl)-phenol (CYASORB® 5411); 2-hydroxy-4-n-octyloxybenzophenone (CYASORB® 5412); * 531);2-[4,6-bis(2,4-dimethylphenyl)-l,3,5-triazin-2-yl]-5-(octyloxy)-phenol (CYASORB * 1164);2,2 * -(l,4-phenylene)bis(4H-3,l-benzoxazin-4-one)(CYASORB * UV-3638;l,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenyl-acryloyl)oxy]methyl]propane (UVINUL * 3030);2,2 *-(l,4-phenylene)bis(4H-3,1-benzoxazin-4-one); l,3-bis[(2-cyano-3,3-diphenylacryloyl)oxy]-2,2-bis[[(2-cyano-3,3-diphenyl-acryloyl)oxy]methyl]propane; or a combination comprising at least one of the foregoing UV absorbers. When a UV absorber is used, the UV absorber may be included in an amount of 0.01 weight percent, or at least 0.05 weight percent, or at least 0.1 weight percent, up to 5 weight percent, or 3 weight percent, or up to 1 weight percent based on the total weight of the composition. For example, the composition may include a UV absorber in an amount of 0.01 to 5 weight percent, or 0.05 to 3 weight percent, or 0.1 to 1 weight percent based on the total weight of the composition.

[0044] The total combined weight of the antioxidant and / or stabilizer may be from 0.1 weight percent, or from 0.2 weight percent, to 5 weight percent, or to 3 weight percent, based on the total weight of the composition. For example, the composition may include the antioxidant and stabilizer in an amount of 0.1-3 weight percent combined. For example, the composition may include the thermal stabilizer in an amount of 0.01-5 weight percent, or 0.05-3 weight percent, or 0.1-1 weight percent, based on the total weight of the composition. For example, the composition may include the antioxidant in an amount of 0.01-5 weight percent, or 0.05-3 weight percent, or 0.1-1 weight percent, based on the total weight of the composition.

[0045] Other Additives The disclosed composition can optionally contain one or more additives, provided that the additives do not adversely affect the desired properties of the composition.Mixtures of additives can also be used.Such additives can be mixed at any suitable time during mixing components to form the composition.

[0046] It should be noted that certain fillers, especially inorganic fillers, such as talc, silica, TiO2, clay, mica, nanofillers, glass fibers, glass flakes, glass spheres, should generally be avoided, as they interfere with the etching step of the composition during electroless plating. For example, if such inorganic particulate species are removed from the composition during the etching process, they may deposit in the etching bath, shortening the life of the bath. Thus, the composition does not contain such fillers, or such fillers are minimized and may be present in an amount of less than 1000 ppm (i.e., parts per million by weight), or less than 500 ppm, or less than 200, or less than 100 ppm, based on the total weight of the composition.

[0047] The composition may further comprise one or more release agents. Examples of suitable release agents include fatty acid esters, amides with long carbon chains, such as ethylene bisstearamide, or pentaerythritol tetrastearate, glycerol mono-, di-, or tristearate, or polyolefins, such as mineral oil, polyethylene, polypropylene, or combinations thereof. These materials can be used in a combined total amount of from 0 weight percent, or from 0.1 weight percent, to 5 weight percent, or to 1 weight percent, or to 0.5 weight percent, based on the total weight of the composition. For example, the release agent can be present in an amount of 0.1 to 1 weight percent, based on the total weight of the composition.

[0048] The composition may further comprise one or more lubricants or plasticizers.There is a lot of overlap between these types of materials, and these materials include, for example, phthalates, such as dioctyl-4,5-epoxy-hexahydrophthalate; tris(octoxycarbonylethyl)isocyanurate; tristearin; difunctional or polyfunctional aromatic phosphates, such as resorcinol tetraphenyl diphosphate (RDP), bis(diphenyl)phosphate of hydroquinone, and bis(diphenyl)phosphate of bisphenol A; poly-alpha-olefins; epoxidized soybean oil; silicones, such as silicone oils (e.g., with a molecular weight of at least 1000 g / mol), such as polydimethylsiloxane (PDMS); mixtures of methyl stearate with hydrophilic and hydrophobic nonionic surfactants, including polyethylene glycol polymers, polypropylene glycol polymers, and copolymers thereof, such as methyl stearate and polyethylene-polypropylene glycol copolymers in suitable solvents; waxes, such as beeswax, montan wax, paraffin wax, etc. These materials can be used in amounts from 0 weight percent, or from 0.05 weight percent, to 5 weight percent, or to 1 weight percent, or to 0.1 weight percent based on the total weight of the composition. For example, as exemplified by silicone oil, the amount of lubricant / plasticizer can be 0-5 weight percent, or 0.1-1 weight percent based on the total weight of the composition. Certain metal oxides can be used to help minimize juicing (i.e., deposition on the mold) of fatty acids or their salts and certain other lubricants or plasticizers. Examples of such metal oxides include magnesium oxide (MgO), calcium oxide (CaO), and zinc oxide (ZnO). The metal oxide particles can have an average particle size of 0.5-5 microns. Larger particle sizes, greater than 10 microns and in other cases greater than 25 microns, can result in undesirable pitting and other blemishes on the plated parts. The metal oxide can have a chloride content of less than 1 weight percent based on the total weight of the metal oxide.The metal oxide can be used in the range of 0 weight percent, or 0.1 weight percent, up to 1 weight percent, or up to 0.5 weight percent, for example, 0.1-1 weight percent, based on the total weight of the composition. The molar ratio of metal oxide to fatty acid can be at least 1:2, or at least 4:5, up to 5:1, or up to 2:1, or up to 1.5:1. For example, the molar ratio of metal oxide to fatty acid can range from 1:2 to 5:1.

[0049] Certain colorants, such as pigments and / or color additives, may also be present. Examples of pigments include, for example, carbon black, certain metal oxides (provided they do not plate out or cause problems during molding of the article or electroless plating); sulfides, such as zinc sulfide; aluminates; sodium sulfo-silicates sulfates, chromates, and the like; zinc ferrite; ultramarine; Pigment Brown 24; Pigment Red 101; Pigment Yellow 119; organic pigments, such as azo, diazo, quinacridone, perylene, naphthalenetetracarboxylic acid, flavanthrone, isoindolinone, tetrachloroisoindolinone, anthraquinone, anthanthrone, dioxazine, phthalocyanine, and azo lakes; Pigment Blue 60, Pigment Red 122, Pigment Red 149, Pigment Red 177, Pigment Red 179, Pigment Red 202, Pigment Violet 29, Pigment Blue. Examples of suitable pigments include Pigment Green 15, Pigment Green 7, Pigment Yellow 147, and Pigment Yellow 150, or a combination comprising at least one of the foregoing pigments. Carbon black is one preferred pigment. The amount of pigment should not be so high as to cause problems during molding or etching. For example, the amount of pigment can be from 0 weight percent, or from 0.01 weight percent, to 2 weight percent, or to 1 weight percent, or to 0.5 weight percent, or to 0.1 weight percent based on the total weight of the composition. For example, carbon black can be used in an amount of 0.01 to 2 weight percent, or 0.01 to 1 weight percent, or 0.01 to 1 weight percent based on the total weight of the composition.

[0050] The compositions disclosed herein can contain less than 20 weight percent, or less than 10 weight percent, or less than 5 weight percent, or less than 3 weight percent, or less than 1 weight percent polycarbonate, based on the total weight of the composition. The compositions can be free of polycarbonate (i.e., can be polycarbonate-free).

[0051] The compositions disclosed herein may be characterized by a melt flow rate according to ISO 1133:2011 of at least 5 g / 10 min at 10 kg and 220° C., or at least 10 g / 10 min, or at least 15 g / 10 min. The compositions disclosed herein may be characterized by a melt flow rate according to ISO 1133 of up to 40 g / 10 min, or up to 35 g / 10 min, or up to 30 g / 10 min at 10 kg and 220° C.

[0052] The compositions disclosed herein have an Izod impact strength according to ISO 180:2011 of at least 15 kJ / m 2 , or at least 20 kJ / m 2 , or at least 25 kJ / m 2 The compositions disclosed herein can be characterized by an Izod impact strength according to ISO 180 of 50 kJ / m 2 or 40kJ / m 2 It can be characterized by being up to

[0053] The compositions disclosed herein may be characterized by a tensile modulus of at least 1500 MPa, or at least 2000 MPa, or at least 2200 MPa. The compositions disclosed herein may be characterized by a tensile modulus of up to 4000 MPa, or up to 3500 MPa. The compositions disclosed herein may be characterized by a tensile yield strength of at least 35 MPa, or at least 40 MPa. The compositions disclosed herein may be characterized by a tensile strength of up to 60 MPa, or up to 55 MPa. The compositions disclosed herein may be characterized by an elongation at break of at least 10%, or at least 20%. The compositions disclosed herein may be characterized by an elongation at break of up to 200%, or up to 150%. Tensile modulus, tensile yield strength, and elongation at break may be measured at 50 mm / min by ISO 527-2012.

[0054] The composition may be characterized by a coefficient of thermal expansion of at least 50 micrometers / m-° C., or at least 60 micrometers / m-° C., or at least 65 micrometers / m-° C. The composition may be characterized by a coefficient of thermal expansion of up to 90 micrometers / m-° C. according to ASTM E831-14 (i.e., 2014).

[0055] The composition may be characterized by a heat deflection temperature (HDT) of at least 75° C. at a force of 1.8 MPa according to ISO 75-2004.

[0056] The composition may be characterized by a Vicat C softening point of at least 90° C. at 50° C. / min according to ISO 306:2004.

[0057] The composition may be characterized by a flexural modulus of 2000-4000 MPa as measured by ISO 178:2010.

[0058] Preparation of the composition The composition can be manufactured by methods generally available in the art. For example, in one embodiment, in one mode of procedure, the components can be first blended in a Henschel high speed mixer or other suitable mixer / blender. Other low shear processes, including but not limited to hand mixing, can also accomplish this blending. This blend can then be fed through a hopper into the throat of a twin screw extruder. Alternatively, one or more of the components can be incorporated into the composition by feeding directly into the extruder at the throat and / or downstream through a downstream side stuffer. Additives and the like can also be compounded into a masterbatch with the desired polymeric resin and fed into the extruder. The extruder can be operated at a temperature higher than that required to cause the composition to flow. The extrudate can be rapidly quenched (e.g., in a water bath) and pelletized. The pellets can be used for subsequent molding, shaping, or forming.

[0059] Articles and their manufacture The compositions can be formed into useful shaped articles by various means, such as, for example, injection molding, additive manufacturing, extrusion, rotational molding, compression molding, blow molding, sheet or film extrusion, profile extrusion, gas-assisted molding, structural foam molding, and thermoforming. The thermoplastic compositions described herein with improved electroplating adhesion can also be made into films and sheets, as well as components of lamination systems. The compositions can be formed into articles by co-molding, overmolding, or laminating with other thermoplastics, such as, for example, polycarbonates, polystyrene blends, poly(meth)acrylates, and the like.

[0060] Articles formed from the compositions can be relatively thin, for example, having a thickness of from 1 mm, or from 2 mm, or from 5 mm, to 20 mm, or to 15 mm. The articles can have an aspect ratio (length and / or weight to thickness) of at least 10.

[0061] The formed thermoplastic article can be plated with metal by known processes such as electroless plating. For example, the surface to be plated can be surface treated. The surface treatment step can include one or more of etching, neutralization, activation, and acceleration. Etching can be done with a strong oxidizing solution such as a mixture of chromium trioxide and sulfuric acid to create a surface structure for good adhesion and / or convert a hydrophobic surface to a hydrophilic surface. In this step, the diene rubber can be selectively removed (etched) at and near the surface. This selective removal can form a recess on the surface to which an adhesion promoter can be attached. After etching, the surface can be rinsed with a neutralizing solution such as sodium bisulfite. An activator (or adhesion promoter), such as an acidic solution of a precious metal (e.g., palladium), can create a catalytic surface for effective plating. The activated surface can then be exposed (e.g., in a bath) to an electroless plating solution to deposit the metal on the catalytic surface. The plating solution can include metal salts, reducing agents, complexing agents, stabilizers, and buffers. Additional metal layers can be applied by repeatedly electroplating a similar or different metal onto the initially deposited metal coating. Rinsing steps, for example in chemical baths, can be used to minimize or avoid chemical contamination between surface treatment steps.

[0062] After etching, an adhesion promoter such as palladium can be mechanically attached to the surface, which then becomes conductive and can bond with metals such as nickel or copper in subsequent electroplating.

[0063] During electroless coating, nickel and / or copper can be coated onto the substrate. During subsequent electroplating, additional metal layers can be added, including metals such as nickel, copper, chromium, cobalt, zinc, or alloys thereof. There may be various layers, for example, a nickel layer, a copper layer, and a chromium layer. According to one preferred structure, starting from the polymer composition, there are layers of nickel, copper, nickel, and chromium in this order.

[0064] The thickness of any one metal layer may be at least 0.5 micrometers, or at least 1 micrometer, or at least 2 micrometers. The thickness of any one layer may be up to 50 micrometers, or up to 40 micrometers, or up to 30 micrometers, or up to 25 micrometers. For example, a single metal layer may have a thickness of 0.5 to 50 micrometers. The total thickness of the metal layer after electrolytic plating may be at least 2 micrometers, at least 5 micrometers, or at least 10 micrometers. The total thickness of the metal layer may be up to 150 micrometers, or up to 120 micrometers, or up to 100 micrometers. For example, the total thickness of the metal layer may be 2 to 150 micrometers. According to one example, the metal coating comprises 2 micrometers of nickel / 20 micrometers of copper / 10 to 20 micrometers of nickel / 0.2 to 5 (or 0.2 to 1) micrometers of chromium.

[0065] A polymeric sealing layer may be applied over the metal top layer. Examples of such polymeric sealing layers include acrylic and / or epoxy coatings, polyurethane coatings, and silica-containing hard coats.

[0066] The plated articles disclosed herein may have a peel strength according to ASTM B533-85 of at least 8 (1401 N / m), or at least 9 (1576 N / m), or at least 10 pounds force per inch (lbf / in) (1751 N / m). The plated articles disclosed herein may have a peel strength of up to 20 lbf / in (3502 N / m).

[0067] The plated articles disclosed herein can exhibit remarkable resistance to thermal cycling without any visible signs of failure, which can be defects such as delamination, bubbles, haze, cracks, etc. The thermal cycling test includes the following steps: 1) Inspect the sample for defects 2) Place the defect-free sample in a -40°F (-40°C) environment for 1 hour. 3) Remove from the cold environment and inspect for defects. 4) Within 2 minutes of removing the specimen from the cold environment, place it in a hot environment at 200°F (93°C) for 1 hour. 5) Remove from the high temperature environment and inspect for defects. 6) Within 2 minutes of removing the specimen from the hot environment, place it in a cold environment at -40°F for 1 hour. 7) Repeat steps 3-6 until defects are detected. The plated article can withstand at least 7 cycles, at least 8 cycles, at least 9 cycles, or at least 10 cycles without defects.

[0068] The metal plated article may have a reflectance of at least 99% as measured by ASTM C1503-08.

[0069] The metal plated articles may be suitable for use in automotive or transportation applications in that they have good gravel chip resistance and good chemical resistance (eg, passing calcium chloride test exposure criteria).

[0070] Plated articles comprising the compositions disclosed herein can be used in transportation (e.g., automotive), electronics, or plumbing applications or devices. For example, for transportation or automotive applications, the article can be or can be used in an article selected from instrument panels, overhead consoles, interior trim, center consoles, panels, quarter panels, rocker panels, trim, fenders, doors, deck lids, trunk lids, hoods, bonnets, roofs, bumpers, fascias, grilles, minor housings, pillar appliques, cladding, body side moldings, wheel covers, hubcaps, door handles, window frames, headlamp bezels, headlamps, tail lamps, tail lamp housings, tail lamp bezels, license plate housings, roof racks, footboards, radio speaker grills, instrument panel bezels, steering columns, drip rails, energy absorbers, kickboards, mirror housings, grill opening reinforcements, stairs, hatch covers, knobs, buttons, and levers.

[0071] As another example, the article may be, or may be a component part of, for example, computer and business equipment housings, household appliances, trays, plates, handles, helmets, plumbing components such as faucets, or shower heads. In various further examples, formed articles include, but are not limited to, power tools, food and beverage service items, medical devices, animal cages, electrical connectors, electrical equipment enclosures, motor parts, power distributors, communications equipment, computers, and the like (including devices molded into snap-fit ​​connectors). Articles of the invention may comprise vehicle body skins, and outdoor or protected graphic components such as signs, outdoor enclosures such as telecommunications and electrical junction boxes, and construction products such as roof sections, wall panels, and glazing. EXAMPLES

[0072] The following materials were used in the examples: Styrene / Acrylonitrile (SAN) - 72% styrene / 28% acrylonitrile, weight average molecular weight (M w ) 150,000 g / mol, number average molecular weight (Mn) 70,000 g / mol. Commercially available as Blendex™ 576 from Galata Chemicals. · Acrylonitrile / Butadiene / Styrene (ABS) Graft Rubber Composition - 21 parts acrylonitrile, 31 parts butadiene, 46 parts styrene, 2 parts methyl methacrylate. The ABS rubber contains an insoluble grafted rubber portion and a non-grafted hard SAN portion. Grafted SAN / Rubber = 52 wt% of the graft rubber composition. The non-grafted (hard extractable) SAN constitutes 48 weight percent of the ABS graft rubber composition and has a weight average molecular weight (Mw) = 120,000 g / mol, and a number average molecular weight (Mn) = 35,000 g / mol. Mw and Mn were determined by GPC using polystyrene standards. The rubber particle size is 300 nm with a broad particle size distribution. The ABS graft rubber contains 6300 ppm tallow fatty acid (TFA) by weight of the ABS rubber. TFA is a mixture of saturated and unsaturated carboxylic acids including myristic acid, linoleic acid, palmitic acid, oleic acid, elaidic acid, and stearic acid. Methyl methacrylate / butadiene / styrene (MBS) core-shell rubber - 13 parts methyl methacrylate / 68 parts butadiene / 17 parts styrene - 175 nm particle size. Commercially available from The Dow Chemical Co. as Paraloid EXL2961A. · Ethylene bis-stearamide, MW 539g / mol, melting point (MP) 145°C. Magnesium stearate, Mw 697g / mol, MP 155°C. Pentaerythritol diphosphite as a stabilizer, MW 605 g / mol. MP 175°C. Available from Addivant Co. as Ultranox 626. Hindered phenol antioxidant. Wingstay L from Omnova. MW 650g / mo. MP 118°C. ·Dimethylsiloxane Polymer – 1000 centipoise viscosity (Momentive). Magnesium oxide (MgO) 390ppm. Particle size less than 1 micrometer. Surface area 160-200m2 / gram, 99% of particles pass 325 mesh. Carbon Black Pigment Grade, 0.035wt%.

[0073] The components were combined in a paint shaker in the amounts of parts by weight shown in Table 1 below, then extruded into pellets at 180-250°C under vacuum in a co-rotating twin screw extruder at approximately 400 rpm. Pellets of the compositions were evaluated for melt flow rate (MFR) at 220°C. Test parts were injection molded from the pellets. The pellets were dried at 95°C for 2 hours and molded at 220-250°C with a cycle time of 25 seconds. Izod impact, tensile modulus and (yield) strength, heat deflection temperature (HDT), and coefficient of thermal expansion (CTE) were measured according to the test methods described above and in Tables 2 and 3. Samples were conditioned at 50% relative humidity and 23°C for at least 2 days prior to testing.

[0074] The articles are electrolessly plated substantially according to the following process, with aeration of the bath and partial rinsing, primarily with water, between each chemical bath: - Immersion wash in Trimax LSAC 349 for 10 minutes, Chromic sulfuric acid etch for 10 minutes at 159°F and pH<10, · 1 minute of Adhemax Neutralizer CR to reduce hexavalent chromium 1 minute pre-activation to maintain HCl concentration Adhemax Activator SF for 4 minutes to nucleate Pd on plastic surfaces Adhemax Accelerator for 2 minutes to accelerate Pd adsorption · 10 minutes of Adhemax EN to deposit electroless nickel 2 minutes of Copper Immersion to add an electroless copper layer Electrolytic copper strike to add a 2-3 micrometer copper layer Standard electroplating process for additional metal layers.

[0075] The injection molded three-dimensional specimen plates were then metallized as described above and tested for thermal shock according to the thermal cycling test described above. The injection molded flat specimen plates were metallized as described above. For the specimens used in the thermal cycling test, the following metal layers were added by electroplating (i.e., electrolytic coating): 25-40 micrometers of copper, semi-bright nickel (10-15 micrometers), bright nickel (8-15 micrometers), microporous nickel (0.5-3.0 micrometers), and chromium (0.25 micrometers). For the adhesion test, the electroplated (i.e., electrolytic coating) metal was a 40-80 micrometer copper layer. Adhesion was determined by peel strength test method ASTM B533-85. As can be seen in Table 2, specimens 1 and 2 containing MBS core-shell rubber survive approximately twice as many thermal shock cycles (11 and 12 cycles) before failure compared to comparative specimen A having only one type of rubber, which failed at 6 cycles. [Table 1]

[0076] [Table 2]

[0077] The present disclosure further includes the following aspects. Aspect 1. An electroless plating composition comprising: 9 to 29 weight percent, preferably 9.7 to 29 weight percent, more preferably 10 to 29 weight percent of a first graft rubber copolymer having a backbone including at least one conjugated diene monomer in polymerized form and at least one monomer selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof, grafted to the backbone, in polymerized form, and preferably comprising an acrylonitrile / butadiene / styrene rubber; 70 to 90 weight percent, preferably 70 to 89.7 weight percent, more preferably 70 to 85 weight percent of an ungrafted styrene polymer, preferably comprising poly(styrene acrylonitrile); 0.1 to 10 weight percent of a core / shell diene rubber having a particle size of 100 to 500 nm; 0.1 to 5 weight percent of a non-grafted styrene polymer having at least one conjugated diene monomer in polymerized form and grafted to the backbone; 1. A composition for electroless plating comprising: one or more stabilizers and / or antioxidants in a total amount of 100 ppm; a fatty acid or a salt of a fatty acid in an amount of 0.1 to 2 weight percent, preferably a fatty acid or a salt of a fatty acid having 8 to 36 carbon atoms; 0 to 5 weight percent of a release agent, preferably a carboxylic acid amide or ester having 8 to 80 carbon atoms; 0 to 1 weight percent of a metal oxide, preferably magnesium oxide, zinc oxide, or calcium oxide, more preferably magnesium oxide; 0 to 3 weight percent of a lubricant, preferably a silicone oil; 0 to 20 weight percent of a polycarbonate, preferably 0 to 10 weight percent of a polycarbonate, more preferably 0 to 5 weight percent of a polycarbonate, even more preferably 0 to 1 weight percent of a polycarbonate, and most preferably 0 weight percent of a polycarbonate, wherein the weight percents and ppm are based on the total weight of the composition.

[0078] Embodiment 2. The composition of embodiment 1, wherein the first graft rubber copolymer comprises an acrylonitrile / butadiene / styrene rubber, the acrylonitrile / butadiene / styrene rubber comprising 55 to 75 weight percent of a backbone derived from butadiene monomer and 25 to 45 weight percent of a copolymer of styrene and acrylonitrile grafted to the backbone.

[0079] Aspect 3. The composition of aspect 2, wherein the weight ratio of styrene to acrylonitrile is from 65:35 to 80:20.

[0080] Aspect 4. The composition of any one of aspects 1-3, wherein the ungrafted styrene polymer comprises poly(styrene acrylonitrile), the poly(styrene acrylonitrile) having 20 to 35 weight percent acrylonitrile and 65 to 80 weight percent styrene, and having a weight average molecular weight of 50,000 to 160,000 g / mol, as measured by gel permeation chromatography (GPC) according to ASTM D5296 using polystyrene standards.

[0081] Aspect 5. The composition of any one of Aspects 1-4, wherein the core-shell diene based rubber has a core comprising a second polymerized conjugated diene monomer and a shell comprising the polymerization product of at least one acrylate monomer and at least one monovinyl aromatic monomer, preferably wherein the amount of conjugated diene monomer is 70 to 95 weight percent, the amount of acrylate monomer is 5 to 29 weight percent, and the amount of monovinyl aromatic monomer is 0.1 to 5 weight percent, the weight percentages being based on the total weight of the core-shell diene based rubber.

[0082] Aspect 6. The composition of aspect 5, wherein the conjugated diene monomer is butadiene, the acrylate monomer is methyl methacrylate, and the monovinyl aromatic monomer is styrene.

[0083] Embodiment 7. The composition of any one of embodiments 1-6, wherein one or more of the stabilizers and / or antioxidants are selected from one or more of a hindered phenol, a phosphorus-containing stabilizer, a sulfur-containing stabilizer, or a combination thereof, and preferably, the composition does not include salts of lead, mercury, thallium, cadmium, barium, or antimony.

[0084] Embodiment 8. The composition of any one of embodiments 1-7, comprising less than 1000 ppm of any of the following materials: titanium dioxide, clay, talc, mica, lead stabilizers, cadmium stabilizers, nanofillers, glass.

[0085] Embodiment 9. The composition of any one of embodiments 1-8, characterized by one or more of: a melt flow rate at 10 kg and 220° C. according to ISO 1133 of 10-40 g / 10 min; an Izod impact according to ISO 180 of 20-50 KJ / sq. meter; a tensile modulus according to ISO 527 of 2000-4000 MPa; a % elongation at break according to ISO 527 of 10-200%; and a coefficient of thermal expansion (CTE) according to ASTM E831-14 of 70-90 um / (m-° C.).

[0086] Aspect 10. The composition of any one of aspects 1 to 9, wherein the amount of ungrafted styrene polymer is from 70 to 90 weight percent, preferably from 70 to 89.7 weight percent, and more preferably from 70 to 85 weight percent, based on the total weight of the composition.

[0087] Aspect 11. The composition of any one of Aspects 1-10, comprising 10-59 weight percent of the acrylonitrile / butadiene / styrene graft rubber composition, 40-60 weight percent of poly(styrene acrylonitrile), 0.1-10 weight percent of a methyl methacrylate / butadiene / styrene core-shell rubber, 0.1-5 weight percent of one or more stabilizers and / or antioxidants, 1000-20,000 ppm of a fatty acid or a salt of a fatty acid having 8-36 carbon atoms, 0-5 weight percent of a mold release agent, 0-1 weight percent of magnesium oxide, zinc oxide, or calcium oxide, 0-3 weight percent of a silicone oil, and 0-5 weight percent of a polycarbonate, wherein the weight percents and ppm are based on the total weight of the composition.

[0088] Embodiment 12. The composition of any one of embodiments 1-11, wherein the total amount of rubber derived from conjugated diene monomers is 10 to 20 weight percent, based on the total weight of the composition.

[0089] Aspect 13. A method of making a composition according to any one of aspects 1-11, comprising providing a graft rubber composition comprising: (a) a first graft rubber copolymer having a backbone including at least one conjugated diene monomer in polymerized form and at least one monomer in polymerized form selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof grafted to the backbone; and (b) an ungrafted polymer of at least one monomer selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof; the first graft rubber composition further comprising: an ungrafted styrene polymer, preferably comprising poly(styrene acrylonitrile); 0.1 to 10 weight percent of a core / shell diene based rubber having a particle size of 100 to 500 nm; 0.1 to 5 weight percent of one or more stabilizers and / or antioxidants in a total amount; 0.1 to 2 weight percent of a fatty acid or a salt of a fatty acid, preferably 8 to 10 weight percent of a fatty acid salt; 1. A method comprising blending a fatty acid or a salt of a fatty acid containing from 36 carbon atoms, 0 to 5 weight percent of a release agent, preferably a carboxylic acid amide or ester having from 8 to 80 carbon atoms, 0 to 1 weight percent of a metal oxide, preferably magnesium oxide, zinc oxide, or calcium oxide, more preferably magnesium oxide, 0 to 3 weight percent of a lubricant, preferably a silicone oil, 0 to 20 weight percent of a polycarbonate, preferably 0 to 10 weight percent of a polycarbonate, more preferably 0 to 5 weight percent of a polycarbonate, and even more preferably 0 to 1 weight percent of a polycarbonate, wherein the weight percents and ppm are based on the total weight of the composition, and the amount of ungrafted styrene polymer is selected such that the amount of ungrafted polymer plus the amount of ungrafted styrene polymer in the grafted rubber composition comprises 70 to 90 weight percent, and all weight percentages are based on the total weight of the composition.

[0090] Embodiment 14. An article comprising the composition of any one of embodiments 1-11 formed into a shape having a surface, the article having a metal coating electrolessly plated onto at least a portion of the surface.

[0091] Example 15. The article of example 14, further having at least one metal coating electroplated over the electrolessly plated metal coating.

[0092] Example 16. The article of example 15, wherein the electrolessly plated metal coating is nickel or copper, and at least one electroplated metal coating comprises one or more of nickel, copper, chromium, cobalt, zinc, or alloys thereof.

[0093] Example 17. The article of example 14 or 16, wherein the metal coating comprises, in order starting from the surface of the composition, a nickel layer and a chromium layer.

[0094] Example 18. The article of any one of examples 14 to 17, comprising the following layers in this order, starting with the polymeric composition: nickel, copper, nickel, chromium.

[0095] Embodiment 19. The article of any one of embodiments 14-18, characterized by one or more of the following: a metal layer peel strength according to ASTM B533 of 8 to 20 pounds-force / inch (1401 to 3502 N / m); the article withstands more than 6 cycles of being placed in a -40°C environment for 1 hour and then a 93°C environment for 1 hour, with no more than 2 minutes between environments, without any visible delamination, bubbles, cracks, or defects in the metal coating.

[0096] Embodiment 20. The article of any one of embodiments 14 to 19, which is a component part of an automobile.

[0097] Embodiment 21. A method for making an article according to any one of embodiments 14-20, comprising forming a composition into a shape and electrolessly plating one or more metals onto a portion of the formed and etched composition.

[0098] Example 22. The method of example 21, further comprising electroplating at least one metal layer over the electrolessly plated metal.

[0099] Example 23 The method of example 21 or 22, wherein forming the composition into the desired shape comprises injection molding.

[0100] The compositions, methods, and articles may alternatively comprise, consist of, or consist essentially of any suitable material, step, or component disclosed herein. The compositions, methods, and articles may additionally or alternatively be formulated to be devoid of, or substantially free of, any material (or species), step, or component that is not otherwise necessary to achieve the function or purpose of the compositions, methods, and articles.

[0101] All ranges disclosed herein are inclusive of the endpoints, and the endpoints can be independently combined with each other (e.g., the range "up to 25 wt.%, more specifically 5 wt.% to 20 wt.%" includes the endpoints of the range "5 wt.% to 25 wt.%, etc.) and all intermediate values. Additionally, the stated upper and lower limits can be combined to form ranges (e.g., "at least 1 wt.%, or at least 2 wt.%" and "up to 10 wt.%, or up to 5 wt.%" can be combined to form the ranges "1 to 10 wt.%", "1 to 5 wt.%", "2 to 10 wt.%", or "2 to 5 wt.%"). "Combinations" include blends, mixtures, alloys, reaction products, and the like. Terms such as "first", "second", and the like are used to distinguish one element from another, but not to denote any order, amount, or importance. The terms "a" and "an" and "the" do not denote limitations of quantity and should be construed to cover both the singular and the plural unless otherwise indicated herein or clearly contradicted by context. "Or" means "and / or" unless expressly stated otherwise. Throughout this specification, references to "some embodiments," "an embodiment," and the like mean that a particular element described in connection with an embodiment is included in at least one embodiment described herein and may or may not be present in other embodiments. In addition, it is to be understood that the described elements can be combined in any suitable manner in various embodiments. "Combinations thereof" is an open-ended phrase and includes any combination that includes at least one of the recited elements or features, optionally together with similar or equivalent elements or features that are not recited.

[0102] Unless otherwise stated herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears.

[0103] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs.All cited patents, patent applications, and other references are incorporated herein by reference in their entirety.However, if a term in this application contradicts or conflicts with a term in an incorporated reference, the term from this application shall take precedence over the conflicting term from the incorporated reference.

[0104] Compounds are described using standard nomenclature. For example, any position that is not replaced by any indicated group is understood to have its valency filled by a bond or hydrogen atom as indicated. A dash symbol ("-") that is not between two letters or symbols is used to indicate the attachment point of a substituent. For example, -CHO is attached through the carbon of a carbonyl group.

[0105] The term "alkyl" refers to a branched or straight chain, unsaturated aliphatic hydrocarbon group, e.g., methyl, ethyl, n-propyl, i-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, s-pentyl, and n- and s-hexyl. "Alkenyl" refers to a straight or branched chain, monovalent hydrocarbon group having at least one carbon-carbon double bond (e.g., ethenyl (-HC=CH2)). "Alkoxy" refers to an alkyl group linked through an oxygen (i.e., alkyl-O-), e.g., methoxy, ethoxy, and sec-butyloxy groups. "Aryl" refers to an aromatic hydrocarbon group containing the specified number of carbon atoms, e.g., phenyl, tropone, indanyl, or naphthyl. The prefix "halo" refers to a group or compound containing one or more fluoro, chloro, bromo, or iodo substituents. Combinations of different halo groups (e.g., bromo and fluoro) may be present, or only chloro groups may be present. The prefix "hetero" means that the compound or group contains at least one ring member that is a heteroatom (e.g., 1, 2, or 3 heteroatoms), where the heteroatom(s) are each independently N, O, S, Si, or P. "Substituted" means that the compound or group is substituted in place of a hydrogen with at least one (e.g., 1, 2, 3, or 4) substituents, each independently selected from the group consisting of C, C- ... 1~9 Alkoxy, C 1~9 Haloalkoxy, nitro (-NO2), cyano (-CN), C 1~6 Alkylsulfonyl (-S(=O)2-alkyl), C 6~12 Arylsulfonyl (-S(=O)2-aryl), thiol (-SH), thiocyano (-SCN), tosyl (CH3C6H4SO2-), C 3~12 Cycloalkyl, C 2~12 Alkenyl, C 5~12 Cycloalkenyl, C 6~12 Aryl, C 7~13 Aryl alkylene, C 4~12 Heterocycloalkyl, and C 3~12It may be heteroaryl. The number of carbon atoms indicated in a group is exclusive of any substituents. For example, -CH2CH2CN is a C2 alkyl group substituted with a nitrile.

[0106] While particular embodiments have been described, presently unforeseen or unanticipated alternatives, modifications, variations, improvements, and substantial equivalents may occur to applicant or others skilled in the art, and it is accordingly intended that the appended claims, as filed and as amended, include all such alternatives, modifications, improvements, and substantial equivalents.

Claims

1. A composition for electroless plating comprising: from 9 to 29 weight percent of a first graft rubber copolymer having a backbone including at least one conjugated diene monomer in polymerized form and at least one monomer in polymerized form selected from monovinyl aromatic monomers, acrylic monomers, and combinations thereof grafted to the backbone, the first graft rubber copolymer comprising an acrylonitrile / butadiene / styrene rubber; 70 to 90 weight percent of an ungrafted styrene polymer, the ungrafted styrene polymer comprising poly(styrene acrylonitrile); 0.1 to 10 weight percent of a core / shell diene-based rubber having a particle size of 100 to 500 nm; one or more stabilizers and / or antioxidants in a total amount from 0.1 to 5 weight percent; a fatty acid or a salt of a fatty acid in an amount of 0.1 to 2 weight percent, the fatty acid or salt of a fatty acid containing from 8 to 36 carbon atoms; 0 to 5 weight percent of a mold release agent; 0 to 1 weight percent metal oxide; 0 to 3 weight percent of a lubricant; comprising 0 to 20 weight percent polycarbonate; An electroless plating composition, wherein the weight percentages and ppm are based on the total weight of the composition.

2. 10. The composition of claim 1, wherein the first graft rubber copolymer comprises an acrylonitrile / butadiene / styrene rubber, the acrylonitrile / butadiene / styrene rubber comprising 55 to 75 weight percent of a backbone derived from butadiene monomer and 25 to 45 weight percent of a copolymer of styrene and acrylonitrile grafted to the backbone.

3. 3. The composition of claim 1 or 2, wherein the ungrafted styrenic polymer comprises poly(styrene acrylonitrile), the poly(styrene acrylonitrile) having an acrylonitrile-derived content of 20 to 35% by weight and a styrene-derived content of 65 to 80% by weight, and a weight average molecular weight of 50,000 to 160,000 g / mol, as measured by gel permeation chromatography (GPC) according to ASTM D5296 using polystyrene standards.

4. The composition of any one of claims 1 to 3, wherein the core-shell diene based rubber has a core comprising a second polymerized conjugated diene monomer and a shell comprising the polymerization product of at least one acrylate monomer and at least one monovinyl aromatic monomer.

5. 5. The composition of claim 4, wherein said second conjugated diene monomer is butadiene, said acrylate monomer is methyl methacrylate, and said monovinyl aromatic monomer is styrene.

6. 6. The composition of any one of claims 1 to 5, wherein one or more of the stabilizers and / or antioxidants are selected from one or more of a hindered phenol, a phosphorus-containing stabilizer, a sulfur-containing stabilizer, or a combination thereof.

7. 7. The composition of any one of claims 1 to 6, characterized by having less than 1000 ppm of any of the following materials: titanium dioxide, clay, talc, mica, lead stabilizers, cadmium stabilizers, nanofillers, glass.

8. Melt flow rate according to ISO 1133 at 10 kg and 220° C. of 10 to 40 g / 10 min; Izod impact according to ISO 180 is 20 to 50 KJ / m2; a tensile modulus according to ISO 527 of 2000 to 4000 MPa; Elongation at break (%) according to ISO 527 is 10-200%; The composition of any one of claims 1 to 7, characterized by one or more of the following: Coefficient of Thermal Expansion (CTE) of 70 to 90 um / (m-°C) according to ASTM E831-14.

9. 9 to 29 weight percent of an acrylonitrile / butadiene / styrene graft rubber composition; 70 to 90 weight percent poly(styrene acrylonitrile); 0.1 to 10 weight percent of a methyl methacrylate / butadiene / styrene core-shell rubber 0.1 to 5 weight percent of one or more stabilizers and / or antioxidants; 1000 to 20,000 ppm of a fatty acid or a salt of a fatty acid containing 8 to 36 carbon atoms; 0 to 5 weight percent of a release agent and / or lubricant; 0 to 1 weight percent of magnesium oxide, zinc oxide, or calcium oxide; 0 to 3 weight percent silicone oil; 0 to 5 weight percent polycarbonate; The composition of any one of claims 1 to 8, wherein weight percentages and ppm are based on the total weight of the composition.

10. 10. An article comprising the composition of any one of claims 1 to 9 formed into a shape having a surface, said article having a metal coating electrolessly plated onto a portion of said surface.

11. Metal layer peel strength according to ASTM B533-85 is 1401 to 3502 N / m; 11. The article of claim 10, characterized by one or more of the following: the article withstands more than 6 cycles of being placed in a -40°C environment for 1 hour and then a 93°C environment for 1 hour, with no more than 2 minutes between said environments, without any visible delamination, bubbles, cracks, or defects in the metal coating.

12. 12. The article of claim 10 or 11, wherein the metal coating comprises, starting from the surface of the composition, a nickel layer and a chromium layer in that order.

13. The article of any one of claims 10 to 12, which is a component part of an automobile.

14. 13. A method for making the article of any one of claims 10-12, comprising forming the composition into a shape, etching the shape with an oxidizing acid, and electrolessly plating one or more metals onto a portion of the formed and etched composition.

15. The method of claim 14, wherein forming the composition into a desired shape comprises injection molding.

Citation Information

Patent Citations

  • A polycarbonate-ABS alloy resin composition excellent in plating adhesion and a molded article containing the same

    JP2018507919A

  • Polycarbonate-ABS based alloy resin composition having superior plating adhesion and molded article including the same

    US20170313870A1

  • Thermoplastic resin composition for plated molded article, and molded article and plated molded article both obtained using same

    WO2019087653A1